2022
DOI: 10.3390/su14169925
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Factors Influencing Preservice Teachers’ Behavior Intention in the Implementation of STEM Education Using Partial Least Squares Approach

Abstract: The integration of STEM education has been promoted to improve the quality of education in the 21st century, with its usage leading to emphasis on the factors influencing the intentions of preservice teachers. Therefore, this study aims to determine the factors influencing preservice teachers’ intentions, as well as the effects of gender and age on the implementation of STEM education. The Theory of Planned Behavior (TPB) was adopted to predict the relationship between knowledge, social influence, attitude, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…The structural model was evaluated by examining the significance of the path coefficients using the bootstrapping technique with 5000 resamples 74 , 75 . The hypothesis was tested using tailed testing because the type of testing was the directional method.…”
Section: Resultsmentioning
confidence: 99%
“…The structural model was evaluated by examining the significance of the path coefficients using the bootstrapping technique with 5000 resamples 74 , 75 . The hypothesis was tested using tailed testing because the type of testing was the directional method.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, Existing research on the relationship between subjective norms and behavioral intention has produced contradictory findings. Others found subjective norms to be significant predictors of behavioral intention (Al-Otaibi & Houghton, 2015;Fernandez et al, 2022;Gopi & Ramayah, 2007;Hsiao & Tang, 2014;Huang et al, 2022), whereas some authors were unable to provide support for the relationship between subjective norms and behavioral intention (Kobylinska, 2022;Wijaya et al, 2022). Perceived behavioral control (PBC) refers to an individual's perceptions of the presence or absence of resources, capability, and a sense of control necessary for the successful performance of a given behavior.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Students are satisfied with their learning experience, they are more likely to continue their education, perform well academically, and achieve their personal and professional goals. A study by Wijaya et al [89] indicated the usefulness of technology for stimulating student satisfaction, even for mathematics, through microlectures covering video-based learning mediums. Overall, technology interface, student engagement, and student satisfaction are interconnected and can have a significant impact on the success and outcomes of students in the field of education.…”
Section: H4mentioning
confidence: 99%